The Conceptual Evolution in Linguistics: implications for the study of Kaaps - Dyers, Charlyn (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
As an academic discipline, Linguistics - the scientific study of language - is associated with a range of concepts. Students of Linguistics are traditionally introduced to these concepts in their first year of study, and everything that follows builds on knowledge of these concepts. But language, as Blommaert (2011) notes, is the most visible sign of social change. Currently, much critical thinking is said to be philosophical outflows of a late or post-modern era, characterized by an intensification of three characteristics that have been part of human history for some time: globalization, migration and the dominant position of English, accompanied by the growth of new hybrid languages in urban spaces. In terms of the ongoing vitality of other languages and the influence of a number of dominant language ideologies (Weber and Horner 2012), these three characteristics have sparked discourses of endangerment, revitalization, commodification and carnivalisation (Duchene en Heller, 2007; Heller, 2010). At the same time, there has been a steady evolution in our understanding of many linguistic concepts, particularly those emanating from particular language ideologies and hierarchical political powers. This paper addresses this issue and its implications for the study and treatment of the colloquial variety of Afrikaans known as Kaaps. The contents of the paper have been slightly modified from the original Afrikaans version which appeared in Kaaps in Fokus.